TERMODINAMIKA DALAM MEMAHAMI PROSES PENGOLAHAN MINERAL - Taruminkeng, Stephanie; Mustopa, Enjang Jaenal; Hendrajaya, Lilik (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Indonesia is a country with abundant natural resources, especially minerals. Mineral processing in Indonesia is mandatory in accordance with government regulations, carried out using metallurgical process consisting of pyrometallurgy (extraction at high temperature), hydrometallurgical (low-temperature extraction through leaching) and electrometalurgi (extraction by utilizing electrochemical principle). For physics, to follow a comprehensive manner is through a thermodynamic wherein the variables (measurable) is involved in the chemical processes. These physical variables need to be controlled in order to obtain optimum mineral output. Thermodynamic equilibrium of a chemical reaction (Gibbs potential) is required to view the thermodynamic variables are interrelated. From this connection, the control is carried out intstrumen gauges, installed in the reactor (smelter) and connected to other equipment (mechanical) which then performs the state change according to what is required so that the process is stable. Keywords: mineral processing, metallurgy, thermodynamic equilibrium, smelter.